Online Arabic Language Teaching Model Based on Collaborative Learning in Indonesian Senior High Schools - Umamah, Maftuhatul; Hifdhiyah, Maulidatul (Journal of Arabic Language Learning and Teaching (JALLT), 2024)
This research focuses on the implementation of online/virtual Arabic language learning at Darul Quran Senior High School in Mojokerto, utilizing the collaborative-based learning model known as "The Group Process Model" in the maharah kitabah (Arabic writing skills). Employing the 5M scientific approach and active learning, the study aims to elucidate: (1) the collaborative-based online learning model for maharah kitabah, (2) the application of this learning model, and (3) its impact on improving students' writing skills. Through a descriptive qualitative approach, data were gathered using interviews, observations, and documentation. Analysis involved data reduction, presentation, and drawing conclusions. Findings revealed the preparation of E-learning Moddle, WAG, and Zoom applications, alongside various learning tools such as syllabi, lesson plans, and online learning guides to support collaborative learning and its assessment. The application of the online Arabic Writing Skill model followed a structured approach, including introductory, core, and closing activities, supplemented by assignments and initial activities using the WAG application and Zoom meetings. Students accessed course materials and assignments via the school's E-learning Moddle. The collaborative learning model in Arabic Writing Skill demonstrated enhanced student outcomes and collaborative problem-solving skills in the classroom.